2005
DOI: 10.1136/jech.2004.031625
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of wife beating in Jordanian refugee camps: reports by men and women

Abstract: W ife beating, the most widespread form of domestic violence, has adverse consequences on the health and wellbeing of women and is a major cause of disability and death in many countries. 1 In the past few years, it has been widely reported in developing countries' contexts, 2 where patriarchal family norms are common. 3 In the Middle East, patriarchal gender relations reinforced by traditional cultural, legal, and perhaps religious legacies may have directly or indirectly influenced the persistence of violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 4 publications
3
51
0
2
Order By: Relevance
“…27 The mean age of women who had ever been emotionally or physically abused was 28 years, which was slightly higher than those who were abused within the last year (26.25 years) or during pregnancy (25.5 years). Women who had been abused also had a lower level of education on average than the general sample: 8.5 years for those who were subjected to abuse during their lifetime and 7.4 years for those who were abused during pregnancy and last year.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…27 The mean age of women who had ever been emotionally or physically abused was 28 years, which was slightly higher than those who were abused within the last year (26.25 years) or during pregnancy (25.5 years). Women who had been abused also had a lower level of education on average than the general sample: 8.5 years for those who were subjected to abuse during their lifetime and 7.4 years for those who were abused during pregnancy and last year.…”
Section: Resultsmentioning
confidence: 90%
“…26 The prevalence of wife-beating in Jordanian refugee camps during a woman's lifetime was 44.7%. 27 Preliminary descriptive findings from this screening study revealed that DV against pregnant refugee women was common, 59% women had ever experienced physical violence, 19.1% experienced physical violence during the past year, 26.2% were subjected to sexual coercion, 16.8% experienced emotional violence, and 11.4% experienced physical violence during pregnancy. 28 To our knowledge, no study has been conducted to investigate the factors associated with DV against women during pregnancy in the Arab region.…”
mentioning
confidence: 87%
“…The study of refugee camp populations used an instrument similar to the WHO questionnaire to measure physical intimate partner violence and found a life-time prevalence of 42.5% [22]. The refugee camp study also included men, of whom 48.9% reported [23].…”
Section: ،٤ ‫ﺍﻟﻌﺪﺩ‬ ‫ﻋﴩ،‬ ‫ﺍﳋﺎﻣﺲ‬ ‫ﺍﳌﺠﻠﺪ‬ ‫ﺍﻟﻌﺎﳌﻴﺔ،‬ ‫ﺍﻟﺼﺤﺔ‬ ‫ﻣﻨmentioning
confidence: 99%
“…A multi-country analysis of Demographic and Health Survey (DHS) data showed that approximately one fifth to one half of women experienced spousal or intimate-partner abuse (Kishor and Johnson 2004). Several scholars have reported on the widespread domestic violence perpetrated against Arab women by their spouses (Douki et al 2003;Khawaja and Twetel-Salem 2004;Khawaja and Barazi 2005;Diop-Sidibe et al 2006;Usta et al 2007). Domestic violence against women is also prevalent in Asia, Europe, and South America (Ellsberg et al 1999;Burazeri et al 2005;Khan and Aeron 2006).…”
Section: Introductionmentioning
confidence: 99%